Manajemen Pembiayaan di Sekolah Luar Biasa dalam Meningkatkan Kualitas Pendidikan: Studi Kasus SLB di Padang - Ilmi Zakiah Amalia; Masduki Ahmad (MANAZHIM, 2023)
Running a private special school has its own difficulties, particularly when it comes to budget management. The effectiveness of an educational institution's financial management will undoubtedly have an influence on raising educational standards. The goal of this study is to examine how special schools handle their finances to raise educational standards. A case study methodology was employed in this qualitative research project at one of the private special schools in West Sumatra's Tanjung Raya sub-district. The foundation's director, the principal, and the treasurer served as the study's subjects. This study employed a variety of data gathering techniques, including documentation, interviews, and observation. The data was then examined via conclusion drawing, data reduction, and data display. According to the findings of this research, Tanjung Raya Special School has not implemented the planning, organizing, executing, and monitoring phases of financial management to their fullest potential. However, principals, teachers, and staff collaborate to manage school funding in order to raise educational standards in terms of infrastructure, amenities, and teacher welfare. Infrastructure and school facilities are in line with national education standards, and the provincial office's policies on teachers' welfare have been changed. It may be said that special school Tanjung Raya is doing its utmost to raise academic standards despite having less funding since they haven't yet gotten BOS grants.